The effectiveness of the application of modern methodologies in technical vocational education - Budai, Gábor (Dunakavics, 2024)
In my study, I examined the applicability and effectiveness of the methodology of technical foundation courses. Within the basic technical education - in secondary education - the subject of machine components provides an overview of the history of components, the technical knowledge to be acquired in public education, the planning of the teaching of the subject and the possible methods of lesson organization. With my test results, I pointed out the importance of choosing the right teaching method, which is related to the students' academic results. I also pointed out that the success of teaching and learning also depends on the extent to which teachers can use ICT tools during education. The first part of the study presents the literature background. The second part of the study contains the test data and conclusions.